THE CORK OAK FORESTS OF AQUITAINE: CONSERVATION VERSUS ECONOMIC REVIVAL - Puyo, Jean-Yves (SUD-OUEST EUROPEEN, 2010)
THE CORK OAK FORESTS OF AQUITAINE: CONSERVATION VERSUS ECONOMIC REVIVAL. The cork oak forests and plantations of Aquitaine were once the source of important communities of craftsmen devoted to cork processing. Two areas, le Marensin in the department of Landes and le Neracais in Lot-et-Garonne, have been enjoying renewed attention for the last decade. This paper aims at showing how these groves now become major stakes all the more since there ate so few of them left worldwide and are targeted by multiple projects aiming at either promoting the value of the landscape, sustaining biodiversity, or supporting traditional knowledge (from raising the cork to transforming it) as well as economic worth. Indeed, production has started anew on a few groves, after it came to a standstill more than forty years ago.
The following values have no corresponding Zotero field: pub-location: 5 ALLEES ANTONIO MACHADO, F-31058 TOULOUSE, FRANCE publisher: PRESSES UNIV MIRAIL
Keywords: Cork oak; Cork oak forests; HERTIAGE-MAKING PROCESS; MARENSIN; NERACAIS